Labour's law? - Elke J. Jahn; Thomas Wagner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2001)
A cross section analysis of 23 OECD members shows that there is an 'antagonistic' relationship between the legal protection of investor interests on the one hand and labour interests on the other: the stronger the legal protection of investor rights in a country, the less developed are the individual and collective rights of labour and vice versa. A main cause for a country's position with respect to this trade off is its type of legal system, specifically whether it belongs to the common law or the civil law family. The established procedures of lawmaking and litigation in civil law countries decrease the organisation and influence costs of large interest groups, and increase their chances of institutionalising the income and protection goals of their members in the form of codified statutes. – – Eine Querschnittsanalyse der Rechtsordnungen von 23 Mitgliedern der OECD zeigt, dass eine 'antagonistische' Beziehung zwischen dem Schutz der Kapitalgeberinteressen (KI) auf der einen und der Arbeitnehmerinteressen (AI) auf der anderen Seite besteht: Je ausgeprägter der Schutz der KI in einem Land ist, desto schwächer ausgebildet sind die Individual- und die kollektiven Organisationsrechte der Arbeitnehmer und umgekehrt. Ein Grund für diese Tendenzen des Rechts scheint vom Grad der Autonomie des Rechtssystems und der Gewaltenteilung eines Landes bestimmt, speziell von seiner Zugehörigkeit zur Familie des Civil oder des Common Law. Die Verfahren der Rechtschöpfung und Rechtsprechung in den Civil Law Ländern senken die Kosten der Einführung regulierender Spezialgesetze ebenso wie die Organisations- und Einflusskosten großer Interessengruppen und erhöhen deren Chance, die Einkommens- und Schutzziele ihrer Mitglieder zu institutionalisieren.
Keywords: K31; J53; 330; Labour Law; Legal Origin; Separation of Powers; Industrial Relations; Arbeitsrecht; Anlegerschutz; Gewaltenteilung; Arbeitsbeziehungen; Interessenpolitik; Vergleich; OECD-Staaten; Rechtsordnung